HEURISTIC EPISTEMOLOGY TO LIMIT DIVISIVENESS - Armstrong, Malcolm C C (Journal of Dharma, 2009)
When contrary truths collide, adherence can potentially lead to divisiveness and sometimes violence. If truth is the goal of enquiry, how is truth to be pursued or adhered to without causing conflict or, worse, violence? To address these concerns, a distinct approach to epistemology is being proffered in the hope that the process of enquiry, deliberation, assent/dissent, and adherence are practised with authenticity. The name given to this new understanding of the role of epistemology is Heuristic Epistemology (HE). This approach comprises of three symbiotic and heuristic modalities, namely, the Triad of Apperception, Appraisal, and Appropriation, undergirded by the understanding that the notion of truth is a type of virtue